French–English bilingual children's tense use and shift in narration. (December 2016) - Hoang, Huong; Nicoladis, Elena; Smithson, Lisa; Furman, Reyhan
Bilingual children sometimes show delays relative to monolinguals on language tasks. In the present studies, we explored whether French–English bilinguals' tense use and shift would show a developmental lag in the context of narration. In Study 1, we showed that both French and English monolinguals showed age-related changes in tense use, with preschoolers preferring the past and adults the present. A developmental lag among bilingual children could therefore take the form of prolonged use of the past tense through middle childhood. In Study 2, we observed tense use in the narratives of French–English bilingual children (8–10 years), as well as French and English monolinguals from the same age group. The bilinguals tended to use more present tense than the monolinguals. In qualitative analyses, bilinguals also used a multitude of expressive strategies, such as exclamations, repetitions and onomatopoeia, that made the stories more vivid. Taken together these results suggest that French–English bilinguals do not present developmental differences from monolinguals in tense use. Instead, they adopt an imagistic narrative style that differs from the monolinguals in multiple ways, including a greater use of the present tense. The adoption of this style might be linked to both bilingualism and a cultural preference among French–English bilinguals.